A state-of-the-art review on MXene-based hybrid nanomaterial for energy storage applications - Praveen Kumar Kanti; Deepthi Jayan K.; Wanatasanappan V.V.; Swapnalin J.; Sharma P.; Banerjee P. (Elsevier Ltd, 2025)
In recent years, interest has been in hybridizing MXenes with other nanomaterials to enhance their energy storage capabilities. The exceptional optoelectronic and electrochemical properties of 2D nanomaterials make them promising contenders for energy storage and harvesting applications. This comprehensive review centers on utilizing MXenes and MXene-based composite materials as electrodes in various energy storage devices, including supercapacitors and batteries. Combining MXene with other 2D materials can create composite electrode materials with superior electrochemical characteristics. The study encompasses recent advancements in developing MXene-based composite electrode materials, addressing self-stacking challenges by exploring diverse categories of 2D materials. MXene-based composite electrode materials are utilized in numerous batteries as cathodes or anodes. Furthermore, this review discusses the potential applications of MXene-based hybrid nanomaterials beyond traditional lithium-ion batteries (LIBs) and as composite electrodes in supercapacitors, including emerging technologies such as sodium-ion batteries (SIBs), potassium-ion batteries (KIBs), and hybrid capacitive deionization systems. Despite MXenes demonstrating excellent conductivity and mechanical stability, their practical use in storage devices faces impediments related to materials' chemistry and fabrication methods. This review concentrates on the ongoing progress in identifying and resolving these challenges, drawing from the latest research studies, to pave the way for developing high-performance devices suitable for practical applications. Ultimately, it offers valuable insights into their role in shaping the future of sustainable energy technologies. ? 2024 Elsevier B.V.